Compressive strength of palm oil clinker lightweight aggregate concrete containing coal bottom ash as sand replacement - Khairunisa, Muthusamy; Nur Farah Aziera, Jamaludin; Mohamad Nurfahmi, Kamaruzzaman; Muhammad Zulhusni, Ahmad; Nur Azzimah, Zamri; Ahmed Mokhtar, Albshir Budiea (Elsevier Ltd, 2021)
This research investigates the effect of coal bottom ash (CBA) content as partial sand replacement on workability and compressive strength of palm oil clinker lightweight concrete. Five types of mixes consisting 0%, 10%, 20%, 30% and 40% CBA as sand replacement were used. Specimens were water cured until the testing age. Compressive strength and water absorption test were conducted at 28 days. Inclusion of 10% CBA produces concrete with the targeted strength. However, excessive use of CBA at 40% should be avoided as it results in significant strength reduction.